2010
DOI: 10.1021/ef100821t
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate-Bearing Sediments from the Krishna−Godavari Basin: Physical Characterization, Pressure Core Testing, and Scaled Production Monitoring

Abstract: Gas hydrate-bearing sediments recovered by pressure coring from the Krishna-Godavari Basin offshore India during the 2006 National Gas Hydrate Program (NGHP) expedition were characterized using the instrumented pressure testing chamber (IPTC). The IPTC studies provided longitudinal profiles of P-and S-wave velocities, electrical conductivity, and undrained penetration resistance. The formation consisted of fine-grained clayey sediments of high specific surface and high plasticity. X-ray images showed horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…11F). These values are close to that of seawater (Yun et al, 2010) reflecting the high porosity of the sediment. Measurements typically could not be completed below the SMI because of the presence of gas in the sediment.…”
Section: Index Propertiessupporting
confidence: 77%
See 1 more Smart Citation
“…11F). These values are close to that of seawater (Yun et al, 2010) reflecting the high porosity of the sediment. Measurements typically could not be completed below the SMI because of the presence of gas in the sediment.…”
Section: Index Propertiessupporting
confidence: 77%
“…The formation of these extremely complex rotational hydrate features that appear to be "twisted" and induced by core rotation during the drilling process, actually may reflect natural conditions because some recovered cores with these rotational hydrates were obtained as push cores, unaffected by drill-bit rotation (M. Holland, personal communication, 2008). However, sampling effects, including effective stress reduction, fracture formation, and hydrate reformation, may be responsible for some coring-related artifacts (Yun et al, 2010). Hydraulic fracturing caused by the advection of pore fluids may have caused some hydrate to form at Site NGHP-01-10 in the KG Basin (Rees et al, 2011).…”
Section: Wj Winters Et Al / Marine and Petroleum Geology 58 (2014)mentioning
confidence: 99%
“…However, some potential is afforded by the volume change that would be expected to be associated with gas hydrate dissociation. Such internal stresses and strains generated by dissociation could enhance formation permeability locally, providing a means for both the further transmission of pressure reductions as well as the flow of gas to the wellbore (Yun et al, 2010a). Nonetheless, whereas it now appears that gas hydrate production from sand reservoirs is conceivable using largely existing processes; it is clear that much more needs to be known, and perhaps fundamentally new approaches developed, to further the prospects of production from elements lower in the gas hydrates resource pyramid.…”
Section: Challenge Of Extending Production Beyond Sand Reservoirsmentioning
confidence: 99%
“…Pressure coring has been used on a number of oceanic expeditions (Schultheiss et al, 2009) stabilizing the core pressure at the pressure the core was collected. Sampling and test equipment, such as the instrumented pressure testing chamber shown in Figure 7a (Yun et al, 2006;Yun et al, 2010b) has been built and instrumented to make measurements on the obtained pressure core without removing the pore pressure. This device can be modified to allow for other measurements to be made, however not all required measurements can be made using this apparatus.…”
Section: Challenges In Laboratory Investigations In Support Of Gas Prmentioning
confidence: 99%
“…The excess pore pressure reduces the effective stress of sediments and the shear strength, which results in shear failure. Because a number of oceanic gas hydrate deposits are classified as low-permeability fine-grained sediments, e.g., Ulleung basin sediments as reported in Kwon et al [16], hydrate deposits in the Gulf of Mexico as reported in Francisca et al [17], and Krishna-Godavari basin in India as reported in Yun et al [18], the generation of excess pore pressure due to hydrate dissociation is known to be the most relevant process responsible for destabilizing hydrate-bearing sediments [10][11][12][13][14][15]. For example, a 1 °C increase in the temperature of hydrate-bearing sediments results in the pore fluid pressure increasing by the order of several megapascals under the no mass flux condition [15,19,20].…”
Section: Gas Hydrate Dissociation As a Trigger Or Primer For Slope Famentioning
confidence: 99%